Trust and reciprocity among international groups: Experimental evidence from Austria and Japan - Kenju Akai; Robert J. Netzer (Osaka University, Institute of Social and Economic Research (ISER), 2009)
This paper aimed to compare the trust and reciprocity levels among international groups by adopting a modified trust game played among groups from Austria and Japan. Our results were as follows: (i) When the groups interacted intranationally, the trust and reciprocity levels among the Austrian and Japanese groups were identical. (ii) When they interacted internationally, the groups tended to display the same trust levels, and the Japanese groups tended to reciprocate more than the Austrian groups as the trust levels of their respective interacting group increased. These results suggest that a heterolytic group norm exists across nationalities. In other words, the trust between groups is identical across nationality, whereas reciprocity between groups differs. The fact that the Japanese display less in-group favoritism only in terms of reciprocity has an important implication in terms of a comparative analysis of group norms, not only between the EU and Japan but also between individualism and collectivism in larger sense.
Keywords: C92; C71; 330; trust game; Group norm; International experiment; Intranational experiment